2011
DOI: 10.1007/s00421-011-2135-5
|View full text |Cite
|
Sign up to set email alerts
|

Acute metabolic responses to a 24-h ultra-marathon race in male amateur runners

Abstract: The study was conducted to evaluate the metabolic responses to a 24 h ultra-endurance race in male runners. Paired venous and capillary blood samples from 14 athletes (mean age 43.0 ± 10.8 years, body weight 64.3 ± 7.2 kg, VO2max 57.8 ± 6.1 ml kg−1 min−1), taken 3 h before the run, after completing the marathon distance (42.195 km), after 12 h, and at the finish of the race, were analyzed for blood morphology, acid–base balance and electrolytes, lipid profile, interleukin-6 (IL-6), high-sensitivity C-reactive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

30
97
2
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(132 citation statements)
references
References 51 publications
(71 reference statements)
30
97
2
3
Order By: Relevance
“…Surprisingly, the plasma C-reactive protein concentration was immeasurably low. Therefore, recovery of plasma C-reactive protein levels possibly occurred during the recovery time after finishing the marathon, as reported by Waśkiewicz et al46 Cytokines, particularly interleukin-1 and interleukin-6, act as endogenous pyrogens in the brain. Interleukin-1 and interleukin-6 stimulate thermogenesis via synthesis of prostaglandins and corticotropin-releasing factors 47.…”
Section: Discussionmentioning
confidence: 52%
“…Surprisingly, the plasma C-reactive protein concentration was immeasurably low. Therefore, recovery of plasma C-reactive protein levels possibly occurred during the recovery time after finishing the marathon, as reported by Waśkiewicz et al46 Cytokines, particularly interleukin-1 and interleukin-6, act as endogenous pyrogens in the brain. Interleukin-1 and interleukin-6 stimulate thermogenesis via synthesis of prostaglandins and corticotropin-releasing factors 47.…”
Section: Discussionmentioning
confidence: 52%
“…This is compatible with an immediate inflammatory and oxidative response. 17,18 In a study by Banzet et al, 19 IL-6 is involved in an exercise-induced increase of hepcidin gene expression, which had been implicated in training-induced iron deficiency. Furthermore, our data also show a significant increase in serum ferritin immediately after the race and 24 hours post-race.…”
Section: Discussionmentioning
confidence: 98%
“…Several studies showed that IL‐6 levels were increased after an ultra‐endurance exercise competition (Waskiewicz et al., ; Nieman et al., ). In our study, elevated IL‐6 levels were not only due to ultra‐endurance exercise‐induced inflammation; they also reflected the contribution of affected skeletal muscles underlined by elevated CK and AST values (Pedersen & Febbraio, ; Waskiewicz et al., ). Moreover, increased HSCTNT and NT‐pro BNP values indicate that the myocardium of the athletes was also affected but not seriously damaged by the competition, which is in line with other studies (Table ) (McLachlan & Mossop, ).…”
Section: Discussionmentioning
confidence: 99%